Pharmacist-Led Interventions for Reducing Polypharmacy and Improving Patient Outcomes: A Systematic Review - Alkhamsan, Abdullah Hamad Wabran; Al khamsan, Ali Hamad Yahya; Zabarah, Mohammed Manea; Alyami, Abdullah Hamad; Qutayshan, Abdallah Mana Hamad; Aldhuwayin, Mohammad Hassan Ali; Aljarah , Saleh Hamad Mohmmad; Al sulaiman , Hadi Hamad Yousef; Almurdif, Faisal Ahmed Mohammed; Alghubari, Hussain Ali Ali (Journal of Ecohumanism, 2024)
Objective: This systematic review aims to evaluate the impact of pharmacist-led interventions on reducing polypharmacy and improving patient outcomes. Given the risks associated with polypharmacy, especially among older adults, pharmacist-led interventions have emerged as a promising strategy to optimize medication management and enhance patient well-being. Methods: A comprehensive search of multiple databases (PubMed, Medline, Embase, and Cochrane Library) was conducted, focusing on studies from 2016 onwards. The inclusion criteria covered randomized controlled trials, cohort studies, and case studies examining pharmacist-led interventions for patients experiencing polypharmacy. Outcome measures included changes in the number of prescribed medications, adherence levels, patient satisfaction, and clinical outcomes. Data were extracted following PRISMA guidelines, with quality assessment performed using the Cochrane Risk of Bias Tool. Results: A total of 20 studies met the inclusion criteria, representing various healthcare settings such as hospitals, nursing homes, and community pharmacies. Findings consistently indicated that pharmacist-led interventions, including medication review, reconciliation, and patient education, were associated with a significant reduction in the number of medications and improvements in clinical outcomes, patient satisfaction, and medication adherence. Quality assessments indicated a moderate-to-high level of evidence across the studies reviewed. Conclusion: Pharmacist-led interventions demonstrate a substantial positive impact on reducing polypharmacy and enhancing patient outcomes. Integrating pharmacists into multidisciplinary care teams may offer an effective strategy for managing complex medication regimens and improving the quality of life for patients with polypharmacy. Further research is recommended to explore long-term outcomes and refine intervention strategies for diverse patient populations.